2008
DOI: 10.1242/jcs.031047
|View full text |Cite
|
Sign up to set email alerts
|

Identity, developmental restriction and reactivity of extralaminar cells capping mammalian neuromuscular junctions

Abstract: Neuromuscular junctions (NMJs) are normally thought to comprise three major cell types: skeletal muscle fibres, motor neuron terminals and perisynaptic terminal Schwann cells. Here we studied a fourth population of junctional cells in mice and rats, revealed using a novel cytoskeletal antibody (2166). These cells lie outside the synaptic basal lamina but form caps over NMJs during postnatal development. NMJ-capping cells also bound rPH, HM-24, CD34 antibodies and cholera toxin B subunit. Bromodeoxyuridine inco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
57
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(60 citation statements)
references
References 80 publications
1
57
0
Order By: Relevance
“…levels, staining was also seen elsewhere, including connective tissue and blood vessels; thus, CTB staining over other GM1-bearing structures is also seen in the upper region of Figure 2A (left panel). DG2 ( Figure 2A, middle panel) showed a staining pattern similar to that of CTB, with particularly pronounced staining in this image of the parajunctional fibroblast, an extralaminar cell that caps the NMJ and also bears the GM1 ligand (32). GalNAcT -/-nerve terminals and other structures were not stained under these conditions, as expected (data not shown).…”
Section: Figuresupporting
confidence: 77%
“…levels, staining was also seen elsewhere, including connective tissue and blood vessels; thus, CTB staining over other GM1-bearing structures is also seen in the upper region of Figure 2A (left panel). DG2 ( Figure 2A, middle panel) showed a staining pattern similar to that of CTB, with particularly pronounced staining in this image of the parajunctional fibroblast, an extralaminar cell that caps the NMJ and also bears the GM1 ligand (32). GalNAcT -/-nerve terminals and other structures were not stained under these conditions, as expected (data not shown).…”
Section: Figuresupporting
confidence: 77%
“…The post-synaptic muscle fibre is shown in yellow, with characteristic postsynaptic folds and clustering of acetylcholine receptors (AChRs; red). Terminal Schwann cells (TSC) are shown in blue and two NMJ-capping cells (kranocytes; see [65]) are shown in magenta. (B) Schematic diagram illustrating the normal innervation pattern of three muscle fibres (yellow) in an adult mammalian muscle.…”
Section: Als Overviewmentioning
confidence: 99%
“…Further work examining the role of heterogeneous glial cell populations in ALS is therefore required. For example, it would be interesting to know whether nonmyelinating terminal Schwann cells and their neighbouring NMJ-capping cells ('kranocytes' [65]) specifically contribute to ALS pathogenesis and early vulnerability of NMJs. This may be particularly important given the emerging role for glial/synaptic interactions in synaptic homeostasis at the NMJ [66,67].…”
Section: Contribution Of Non-neuronal Cell Types To Synaptic Pathologmentioning
confidence: 99%
“…It has been suggested that the PSC-associated extracellular matrix may play a role in guiding nerve terminal sprouts at the frog NMJ (Chen and Ko 1994;Ko and Chen 1996; see below). Interestingly, fibroblast-like cells (kranocytes) capping the NMJ have also been shown (Connor and McMahan 1987;Court et al 2008).…”
mentioning
confidence: 99%